Very Compact and Broadband Active Antenna for VHF Band Applications - Y. Taachouche; F. Colombel; M. Himdi (International Journal of Antennas and Propagation)
An active receiving antenna with small size consisting of a monopole loaded with a transistor bipolar is presented in this paper. A transistor is used in order to miniaturize the receiving active antenna size in VHF band. The vertical size of the structure is equal to λ/175, where λ is the wavelength at the lower frequency of the bandwidth. Despite the very small size of the antenna, the frequency bandwidth is very wide and the gain is suitable for FM application with sensitive receivers.